Invalid women : figuring feminine illness in American fiction and culture, 1840-1940 - Price Herndl, Diane, 1959- (Chapel Hill : University of North Carolina Press, 1993)
In this imaginative work of cultural and literary history, Diane Price Herndl examines the tensions found in literary representations of feminine illness. Using medical texts, art, and advertising as well as major works of fiction, Price Herndl argues that such representations were not "natural" but were instead ideologically motivated. While invalid women in American fiction sometimes upheld and sometimes challenged dominant social and medical practice, Price Herndl contends that the discourse of feminine illness was a battleground for powerful forces that sought to define women's role in society even after feminism's emergence. The figure of the invalid female must, she says, be understood as a highly politicized figure. Price Herndl looks first at mid-nineteenth-century medical theories that defined women as fundamentally "invalid." She then turns to important literary texts, including works by Harriet Beecher Stowe, E.D.E.N. Southworth, Laura Curtis Bullard, Washington Irving, Edgar Allan Poe, and Nathaniel Hawthorne, to show that male and female authors represented invalid women differently. Price Herndl contends that the figure of the ill woman conveniently resolved problems of the changing culture for nineteenth-century authors of both sexes. Price Herndl then traces the image of invalid women from the turn of the century to World War II, using texts by Charlotte Perkins Gilman, Edith Wharton, Ellen Glasgow, Henry James, F. Scott Fitzgerald, and Tillie Olsen, as well as the film Dark Victory. Despite dramatic changes in both medical practices and women's place in society, fictional representations remained strikingly stable and politically conservative, Price Herndl argues, even when the author's intent was otherwise
Reading Illness. Invalid Ideology. Culture, Dialogue, and Discourse. Invalid Women -- Ch. 1. Defining the Feminine/Defining the Invalid: Women and Medicine in the Mid-Nineteenth Century. Women's Health in the Mid-Nineteenth Century. Physicians and Women. Medical Discourse, Cultural Definition -- Ch. 2. The Threat of Invalidism: Responsibility and Reward in Domestic and Feminist Fiction. Fiction Figuring Women. Invalid Mothers. The Feminist Invalid -- Ch. 3. (Super) "Natural" Invalidism: Male Writers and the Mind/Body Problem. The Domestic and the Romantic (Super)Natural. The Mind/Body Problem. Making Natural Art of Women. The Natural Pharmakon in the Garden. A Return to the Garden: The Healthy Invalid. The "Feverish Poet" -- Ch. 4. The Writing Cure: Women Writers and the Art of Illness. Mental Healing at the Turn of the Century. The Writing Cure. The Art of Illness. Happy Endings -- Ch. 5. Fighting (with) Illness: Success and the Invalid Woman. Success and the Invalid Woman. Success, Class, and Health. Failing Health. Invalid Men and the Ideology of "Separate Spheres" -- Ch. 6. Economics of Illness: Working the Invalid Woman. Willpower. Clinical Ethics and the Invalid Economy. Conclusion: Invalidism and the Female Body Politic. The Political Representation of Feminine Illness.
Includes bibliographical references (pages 245-261) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: American fiction -- 19th century -- History and criticism; Women and literature -- United States -- History -- 19th century; Women and literature -- United States -- History -- 20th century; American fiction -- 20th century -- History and criticism; Women with disabilities -- United States -- History; Women with disabilities in literature; Invalids in literature; Diseases in literature; Sick in literature; Medicine in literature; Women; Women -- Health and hygiene; Medicine in Literature; Literature, Modern -- history; Women; Women's Health; United States; Roman américain -- 19e siècle -- Histoire et critique; Femmes et littérature -- États-Unis -- Histoire -- 19e siècle.; Femmes et littérature -- États-Unis -- Histoire -- 20e siècle.; Roman américain -- 20e siècle -- Histoire et critique; Femmes handicapées -- États-Unis -- Histoire; Handicapées dans la littérature.; Personnes handicapées dans la littérature.; Maladies dans la littérature.; Malades dans la littérature.; Médecine dans la littérature.; Femmes; Femmes -- Santé et hygiène.; women (female humans); LITERARY CRITICISM -- American -- General; Women -- Health and hygiene; Women; Medicine in literature; American fiction; Diseases in literature; Invalids in literature; Sick in literature; Women and literature; Women with disabilities; Women with disabilities in literature; United States; 1800-1999; Criticism, interpretation, etc; History